PRAGMATICS OF BREADCRUMBING: IMPLICATURE AND MAXIM VIOLATIONS IN MANIPULATIVE COMMUNICATION - Fitriani, Raisya Nur; Sudarwati, Emy (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study examines the role of conversational implicatures and maxim violations in manipulative communication, particularly in the phenomenon of breadcrumbing. Breadcrumbing is a subtle manipulation tactic in romantic relationships characterized by ambiguous messages to maintain someone's interest without commitment. Using a qualitative content analysis approach, data were collected through an open-ended online questionnaire aimed at individuals who had experienced breadcrumbing. By applying Grice's implicature theory, this study identifies how maxim violations (quantity, quality, relation, and manner) contribute to creating ambiguity and false hope in breadcrumbing. These deliberate violations aim to maintain an emotional connection while avoiding clear intentions in the relationship, thereby preserving ambiguity within it. The findings reveal that perpetrators of breadcrumbing often use vague and unclear language as a communication manipulation strategy that creates emotional uncertainty in the victim. This study also highlights the psychological impact of breadcrumbing on victims, such as emotional uncertainty and decreased self-esteem. The work emphasizes the value of pragmatic linguistic analysis in uncovering subtle forms of emotional manipulation in romantic relationships and suggests potential strategies for awareness and prevention.